2003
DOI: 10.1152/ajplung.00270.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nitric oxide production in limb and ventilatory muscles during chronic exercise training

Abstract: study, we evaluated the differential influence of chronic treadmill training (30 m/min, 15% incline, 1 h/day, 5 days/wk) on nitric oxide (NO) production and NO synthase (NOS) isoform expression as well as 3-nitrotyrosine formation (footprint of peroxynitrite) both in limb (gastrocnemius) and ventilatory (diaphragm) muscles. A group of exercise-trained rats and a control group (no training) were examined after a 4-wk experimental period. Exercise training elicited an approximate fourfold rise in gastrocnemius N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
3
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 28 publications
6
60
3
4
Order By: Relevance
“…nNOSμ expression and activity increased in the hindlimb and respiratory muscles of rats subjected to long-term treadmill running or swimming (Balon and Nadler 1997;TatchumTalom et al 2000;Vassilakopoulos et al 2003). Skeletal muscle nNOSμ expression declines with age in rats, suggesting that sarcopenia may be linked with the downregulation of nNOSμ (Song et al 2009), but long-term treadmill running has been found to reverse this age-related decrease in nNOSμ expression (Song et al 2009).…”
Section: Nnos and Skeletal Muscle Adaptation To Exercisementioning
confidence: 99%
“…nNOSμ expression and activity increased in the hindlimb and respiratory muscles of rats subjected to long-term treadmill running or swimming (Balon and Nadler 1997;TatchumTalom et al 2000;Vassilakopoulos et al 2003). Skeletal muscle nNOSμ expression declines with age in rats, suggesting that sarcopenia may be linked with the downregulation of nNOSμ (Song et al 2009), but long-term treadmill running has been found to reverse this age-related decrease in nNOSμ expression (Song et al 2009).…”
Section: Nnos and Skeletal Muscle Adaptation To Exercisementioning
confidence: 99%
“…In rat skeletal muscle myoblasts, the IL-1β-mediated iNOS induction was reduced by blocking ERK1/2 activation and completely abolished by the inhibition of NFκB. Increased iNOS mRNA level after an acute bout of exercise in rat skeletal muscles has been reported by some authors [117,132] , but not others [134] . However, the role of iNOS is controversial because it is often coexpressed with pro-inflammatory cytokines and adhesion molecules causing muscle inflammation and wasting.…”
Section: Exercise Activation Of Redox Signaling Pathwaysmentioning
confidence: 85%
“…The role of NO is commonly related to vasodilation of the endothelium to facilitate the coming of nutrients distribution to the active muscles as well as the removal and transport of metabolites, maintaining cellular homeostasis 43,44 . Studies using animals showed that 4 and 8 weeks of treadmill running training 47,48 as 4 weeks of swimming training 49 can upregulate nNOS levels in the skeletal muscle of trained mice. On the other hand, studies with humans are not clear in showing if there is an increase in the levels of nNOS and NO in skeletal muscle in response to exercise 45,46 .…”
Section: Physical Exercise Nitric Oxide Synthesis and Glucose Uptakementioning
confidence: 99%